2019
DOI: 10.1093/mnras/stz1895
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray feedback in the FIRE simulations: constraining cosmic ray propagation with GeV γ-ray emission

Abstract: ABSTRACT We present the implementation and the first results of cosmic ray (CR) feedback in the Feedback In Realistic Environments (FIRE) simulations. We investigate CR feedback in non-cosmological simulations of dwarf, sub-L⋆ starburst, and L⋆ galaxies with different propagation models, including advection, isotropic, and anisotropic diffusion, and streaming along field lines with different transport coefficients. We simulate CR diffusion and streaming simultane… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
202
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(235 citation statements)
references
References 133 publications
(218 reference statements)
33
202
0
Order By: Relevance
“…In a cosmic-ray-pressure-dominated halo, cool, warm, and hot gas phases can exist at the same gas density (Ji et al 2020). Although there are few observational constraints of cosmic-ray pressures in the CGM, simulations predict that a cosmic-ray-pressure-dominated halo could be consistent with existing γ-ray observations (Chan et al 2019;Ji et al 2020).…”
Section: The Cgm Pressure Problemmentioning
confidence: 88%
See 1 more Smart Citation
“…In a cosmic-ray-pressure-dominated halo, cool, warm, and hot gas phases can exist at the same gas density (Ji et al 2020). Although there are few observational constraints of cosmic-ray pressures in the CGM, simulations predict that a cosmic-ray-pressure-dominated halo could be consistent with existing γ-ray observations (Chan et al 2019;Ji et al 2020).…”
Section: The Cgm Pressure Problemmentioning
confidence: 88%
“…The cosmic-ray transport models considered in this work are simplified approximations of two different regimes: pure streaming or pure diffusion. Realistically, both streaming and diffusion should happen, to different degrees, simultaneously, and there are recent algorithms that can handle the two selfconsistently (Jiang & Oh 2018;Chan et al 2019;Thomas & Pfrommer 2019). Furthermore, unresolved microphysics alter the local cosmic-ray diffusion coefficient (Farber et al 2018) and the dominant scattering mechanisms that determine cosmic-ray streaming parameters (see Hopkins et al 2020b and references therein for a detailed comparison).…”
Section: Limitations Of Idealized Setupmentioning
confidence: 99%
“…The "MHD" run includes magnetic fields, anisotropic thermal conduction, and viscosity, and the "CR" run includes all these processes plus the "full physics" treatment of stellar cosmic rays (CRs). The CR simulation assumes a diffusion coefficient || k =3 10 29 cm −2 s −1 , which was calibrated to be consistent with observational constraints from γ−ray emission of the MW and some other nearby galaxies (Chan et al 2019;Hopkins et al 2020). Ji et al (2020) showed that CRs can potentially provide a large or even dominant nonthermal fraction of the total pressure support in the CGM of low-redshift ∼L * galaxies.…”
Section: Quantitative Comparison In the Cgm Variation Betweenmentioning
confidence: 90%
“…Komarov et al 2014;Su et al 2017a;Hopkins et al 2019;Su et al 2019). On the other hand, CR pressure could be responsible for supporting the diffuse cool CGM (Salem, Bryan & Corlies 2016;Butsky & Quinn 2018), driving galactic outflows (Ruszkowski, Yang & Zweibel 2017;Wiener, Oh & Zweibel 2017;Chan et al 2019), or heating the CGM via excitation of short-wavelength Alfvén waves (Wiener, Peng Oh & Zweibel 2013), and its nonlinear effects on CGM structure in a fully cosmological setting remain largely unexplored. Especially, Salem et al (2016) found that CRs can provide significant pressure support for CGM, while they did not include non-adiabatic CR energy loss terms which are very important in regimes of low CR diffusion coefficients or high gas densities (e.g.…”
mentioning
confidence: 99%
“…To explore the impact of the non-thermal components on the CGM in a more self-consistent manner, we utilize a new series of high-resolution fully cosmological simulations from the Feedback in Realistic Environments (FIRE) 2 project (Hopkins et al 2014), including magnetic fields, physical conduction and viscosity, and explicit CR transport and CR-gas interactions including collisional (hadronic+Coulomb) and streaming losses of CR energy (Chan et al 2019;Hopkins et al 2019;Su et al 2019). Previous FIRE simulations, ignoring explicit CR transport, have been used to explore and predict CGM properties such as high-redshift HI covering factors (Faucher-Giguère et al 2015, the nature of the cosmic baryon cycle and outflow recycling (Muratov et al 2015;Anglés-Alcázar et al 2017;Hafen et al 2018), statistics of low-redshift Lyman limit systems (Hafen et al 2017), galaxy outflow properties and the metal budget of the CGM (Ma et al 2015;Muratov et al 2017), the SZ effect and halo baryon fractions (van de Voort et al 2016), and temperature/density/entropy profiles of massive haloes and clusters (Su et al 2019).…”
mentioning
confidence: 99%